Sustainable Everyday Life and Celebrity Environmental Advocacy in Hugh's War on Waste. Issue 6 (18th August 2019) - Craig, Geoffrey
ABSTRACT: This study employs Hugh Fearnley-Whittingstall's television program, Hugh's War on Waste, to explore representations of sustainable everyday life and the functions of celebrity environmental advocacy. The analysis is located within broader understandings of the discursive and contested nature of sustainability and the representative functions of environmental celebrities who act as figures of both distinction and equivalence. It discusses Fearnley-Whittingstall within the context of the stable of celebrity chefs, and it demonstrates how Hugh's War on Waste is an example of the burgeoning televisual genre based on forms of campaigning about food issues. The analysis specifically explores how Hugh's War on Waste is informed by: narratives of self-transformation where individuals are marshaled into appropriate practices of waste management and sustainability, presentations of the pleasures associated with such practices, and revelations of the networks of food production, distribution and consumption across the contexts of domestic everyday life, farms, supermarkets, and other corporations.